Insight into the herbicide resistance patterns in Lolium rigidum populations in Tunisian and Moroccan wheat regions - El-Mastouri, Zakia; Košnarová, Pavlína; Hamouzová, Kateřina; Alimi, Ezzedine; Soukup, Josef (Frontiers in Plant Science, 2024)
Rigid ryegrass (Lolium rigidum Gaud.) is one of the most troublesome weeds in Moroccan and Tunisian cereal crop fields. In total, 19 rigid ryegrass field populations were randomly selected in northern wheat crop areas of Morocco and Tunisia to examine the patterns of herbicide resistance to acetolactate synthase (ALS)- and acetyl-CoA carboxylase (ACCase)-inhibiting herbicides. Greenhouse experiments confirmed reduced sensitivity to ALS- and/or ACCase-inhibiting herbicides in all L. rigidum populations. The occurrence of target-site resistance (TSR) was tested using high-throughput genotyping. The advent of next-generation sequencing (NGS) has enabled easy identification of causal mutations and confirmed the presence of ALS and ACCase mutations at specific codons conferring TSR. Thirteen populations showed resistance to ALS-inhibiting herbicides associated with point mutations in positions Pro-197-Thr, Pro-197-Ser, Pro-197-Leu, Pro-197-Gln and Trp-574-Leu, while resistance to ACCase-inhibiting herbicides was detected in 18 populations in positions Asp-2078-Val, Trp-2027-Cys, Ile-1781-Leu, Gly-2096-Ala, and Ile-2041-Asn of the enzymes conferring TSR. Additionally, dose–response experiments with pyroxsulam applied after the inhibition of cytochrome P450 monooxygenase by malathion showed an increase in sensitivity in two out of seven highly resistant (HR) rigid ryegrass populations. This demonstrates the presence of non-target-site resistance (NTSR) in some ryegrass populations. Further evidence of NTSR was investigated in dose–response experiments with pyroxsulam, following pretreatment with the glutathione S-transferase (GST) inhibitor 4-chloro-7-nitrobenzoxadiazole (NBD-Cl), which partially reversed resistance in only a few individuals of two L. rigidum populations. Hence, our study confirms the existence of multiple and cross-resistance to ALS- and ACCase-inhibiting herbicides in L. rigidum from Morocco and Tunisia with both TSR and NTSR mechanisms. These results emphasize local resistance management as an important tool to detect and mitigate gene flow from rigid ryegrass populations where resistance has evolved.